Electronic Voting and Democracy
XIV, 309 p.
Keywords: Electronic and internet voting has become increasingly widespread in recent years, but which countries are the leaders of the movement and who lags behind? Is the digital divide likely to present a permanent challenge to electronic democracy? What are the experiences with regard to online voting, and what are the arguments for and against? Electronic Voting and Democracy examines these issues and the contexts in which they are played out, such as problems of legitimacy and the practical considerations that have driven some countries toward electronic voting faster than others.